Coastal Louisiana risk assessment model : technical description and 2012 coastal master plan analysis results - Fischbach, Jordan R. (Technical report (Rand Corporation), 2012)
"Motivated by the devastating effects of Hurricanes Katrina and Rita in 2005 and Gustav and Ike in 2008, planners and policymakers in the State of Louisiana have updated the state's Comprehensive Master Plan for a Sustainable Coast (the "Master Plan"). The resulting Master Plan proposes a range of risk reduction and coastal restoration projects to reduce storm surge flood risks to coastal communities and address other objectives to help create a more sustainable coast over the next 50 years. To support this process, the Coastal Protection and Restoration Authority of Louisiana asked RAND to create an analytical model, the Coastal Louisiana Risk Assessment (CLARA) model, to estimate flood depths and damage that occurs as a result of major storms. CLARA made it possible to systematically evaluate potential projects for inclusion in the Master Plan on the basis of how well they reduce flood damage in Louisiana's coastal region. CLARA was also used to evaluate the flood damage reduction provided by the final Master Plan. Results from this analysis show that storm surge flood damage represents a major threat to coastal Louisiana and that, if no action is taken, this damage can be expected to grow substantially in the future. Implementing the Master Plan, however, could substantially reduce future damage. For instance, average annual damage is projected to increase to between $7 billion and $21 billion per year by 2061 in a future without action, but, with the Master Plan in place, this damage level is reduced to between $3 billion and $5 billion."--Provided by publisher